2021
DOI: 10.3390/ijms22052389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Decellularization Protocols to Generate Peripheral Nerve Grafts: A Study on Rat Sciatic Nerves

Abstract: In critical nerve gap repair, decellularized nerve allografts are considered a promising tissue engineering strategy that can provide superior regeneration results compared to nerve conduits. Decellularized nerves offer a well-conserved extracellular matrix component that has proven to play an important role in supporting axonal guiding and peripheral nerve regeneration. Up to now, the known decellularized techniques are time and effort consuming. The present study, performed on rat sciatic nerves, aims at inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…After functionalization, SIRC and hADSCs were trypsinized and carefully seeded on the surface of the DL (170,000 cells per cm 2 of sample). To promote attachment, cells were resuspended in a minimal amount of medium (50 µL) and DLs were immobilized using agarose casts, as previously reported [38]. In order to induce epithelial differentiation of both cell types seeded on the RL, these tissues were cultured for 21 days in EM epithelial differentiation medium containing epithelial growth and differentiation factors, as previously described [39].…”
Section: Generation Of Recellularized Limbal Substitutes By Tissue Engineeringmentioning
confidence: 99%
“…After functionalization, SIRC and hADSCs were trypsinized and carefully seeded on the surface of the DL (170,000 cells per cm 2 of sample). To promote attachment, cells were resuspended in a minimal amount of medium (50 µL) and DLs were immobilized using agarose casts, as previously reported [38]. In order to induce epithelial differentiation of both cell types seeded on the RL, these tissues were cultured for 21 days in EM epithelial differentiation medium containing epithelial growth and differentiation factors, as previously described [39].…”
Section: Generation Of Recellularized Limbal Substitutes By Tissue Engineeringmentioning
confidence: 99%
“…This glycoprotein supports Schwann cell migration and proliferation, being an essential substrate for the Büngner band formation process (Chernousov et al, 2008;Jessen and Mirsky, 2016). Here, an abundant and properly distributed preservation of laminin was successfully achieved with the three new decellularization techniques, being these results considerably better than SD group and comparable to use of similar procedures (El Soury et al, 2021;Garcia-Garcia et al, 2021). Finally, the wellpreservation of the ECM obtained with P1, P2 and SD, as well as the alterations in P3, were well-confirmed by ultrastructural analyses (SEM and TEM).…”
Section: Discussionmentioning
confidence: 74%
“…and atropine (Pfizer, New York, NY, United States, 0.05 μg/g body weight) and then euthanized by an intraperitoneal injection of Eutanex ® solution (0.5 mL/animal). Subsequently, ~3 cm of both sciatic nerves (n = 70 nerves) were removed and cryopreserved (10% DMSO in fetal bovine serum at −80 °C) until use as previously described (Chato-Astrain et al, 2020b;El Soury et al, 2021;Garcia-Garcia et al, 2021;Contreras et al, 2022).…”
Section: Nerve Isolation and Chemical Decellularizationmentioning
confidence: 99%
“…Although SDS and SDC are the most common ionic detergents used for decellularization [ 31 ], we also tested the efficacy of the organic solvent tri-n-butyl phosphate (TnBP), which is known to dissolve lipids while minimally affecting proteins [ 32 ]. Nerve tissue is rich in lipids, mainly in a form of myelin produced by Schwann cells, and a recent study shows that TnBP is more effective than SDS for decellularization of the rat sciatic nerve [ 33 ]. Our data suggested that TnBP did not efficiently remove growth-inhibitory MAG [ 34 ] from the nerve tissue, and the resulting P3 hydrogels induced apoptosis of the Schwann cells in 3D cultures.…”
Section: Discussionmentioning
confidence: 99%